Fostering Green Innovation in Organizations : Accompanied Opportunities and Challenges - Shamsuzzoha, Ahm; Tran, Giang; Jovanovski, Bojan (IEOM Society International, 2022)
The concept of green innovation has been increasingly gaining attention among academics, practitioners, and policymakers, although its way of adoption remains unclear. This study tried to address this gap by providing ways to foster green innovation in organizations. In addition, this study aims to discuss various factors that enable green innovation and accompanying opportunities from this initiative. Moreover, inherent challenges to promoting green innovation in organizations are also elaborated within the scope of this study. Furthermore, this study examines the moderating role of green innovation concerning higher education institute (HEI) and vocational education and training (VET) capabilities and environmental dynamism. This study is concluded after exploring the significance of capability between green dynamic capability and green innovation adoption. We believe that this study opens up a new avenue in the area of green and sustainable innovation and contributes to the environmental literature in general.
Keywords: Green innovation; environmental sustainability; HEI; VET; European Commission; fi=Tuotantotalous|en=Industrial Management|